Role of Gliricidia sepium in Improving Aggregate Stability of Ultisol Limau Manis Padang: A LABoratory study - Yulnafatmawita Yulnafatmawita; Asmar Asmar; Vitria Purnamasari (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2012)
There is no much public concern about soil aggregate stability improvement of a soil. This is due to the fact that it does not directly affect crop yield for a short term, but it determines sustainable agriculture and development for a long term. This research was aimed to investigate soil physical properties especially soil aggregate stability of Ultisols after fresh OM application, then to determine the exact OM dosage to improve the stability. Ultisols used was from Limau Manis (± 367 m asl), an area in lower footslope of Mount Gadut, having wet tropical rainforest. Due to land use change, farming activities in that sloping area could enhance erosion process in the environment. Therefore, efforts to anticipate the erosion must be found. Fresh OM applied was Gliricidia sepium which was found plenty in the area. Five levels of fresh Gliricidia sepium, were 0, 5, 10, 15, and 20 t/ha. Top soil (0-20 cm depth) was mixed with OM, then incubated for 3 months in glasshouse. The results after a 3-month incubation showed that SOM content did not statistically increase, but it improved based on the criteria, from very low to low level as OM was applied for ≥ 10 t/ha. It seemed that 10 t/ha Gliricidia sepium was the best dosage at this condition. There was a positive correlation between SOM content and aggregate stability index of Ultisols after fresh Gliricidia sepium addition.Keywords: Ultisols, soil aggregate stability, soil organic matter content